1987
DOI: 10.1177/104649648701800404
|View full text |Cite
|
Sign up to set email alerts
|

Marathon Group Counseling With Illicit Drug Abusers

Abstract: This study compares the effects offive 16-hour unstructured marathon groups with the effects of five, matched, randomly selected control groups. The five marathons were compared with the five control groups on a semantic differential that consisted of the specific adjective pairs and the evaluative scale of the concept My Real Self. The marathon group members rated some of the adjectivepairs of My Real Self differently and rated the evaluative scale of My Real Self higher than the control group members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Extended sessions in ongoing group therapy have resulted in increased openness, intimacy, cohesion, and a decrease in rigidity (Allen, 1990). Other studies have found that therapeutic confrontation can be achieved and in fact be a preferred level of interaction with the marathon structure (Page, Davis, Berkow, & O'Leary, 19891, that communication involving interpersonal risk is a frequent mode of interaction (Page, 19821, that drug users as group members more frequently initiate therapeutic interactions and generate feedback than in 3a comparison groups (Page & Bridges, 19831, and that marathon groups can have a positive effect on the way drug users perceive themselves (Page, Richmond, & de la Serna, 1987).…”
Section: Marathon Group Therapy With Drug-abuse Populationsmentioning
confidence: 99%
“…Extended sessions in ongoing group therapy have resulted in increased openness, intimacy, cohesion, and a decrease in rigidity (Allen, 1990). Other studies have found that therapeutic confrontation can be achieved and in fact be a preferred level of interaction with the marathon structure (Page, Davis, Berkow, & O'Leary, 19891, that communication involving interpersonal risk is a frequent mode of interaction (Page, 19821, that drug users as group members more frequently initiate therapeutic interactions and generate feedback than in 3a comparison groups (Page & Bridges, 19831, and that marathon groups can have a positive effect on the way drug users perceive themselves (Page, Richmond, & de la Serna, 1987).…”
Section: Marathon Group Therapy With Drug-abuse Populationsmentioning
confidence: 99%